COMMUNICATIVE LANGUAGE TEACHING FOR ELEMENTARY SCHOOLS IN INDONESIA: JOYFUL LEARNING THROUGH GAMES - Istiqomah, Faizatul (Jurnal Bahasa Lingua Scientia, 2010)
English has been taught in Elementary schools since many years ago. But, the effectiveness of teaching English in Elementary school practically is still debatable. Many factors influence, such as the quality of teachers, the methods used, the media applied, and the atmosphere developed. This article introduces an English teaching method called the Communicative Language Teaching (CLT) to be used in teaching English to young learners. This method provides a joyful learning through some games suit to the young learner?s characteristic.